Casas da Tabela. A evolução dos bairros operários em Guimarães - João Freitas Fernandes Martins (2020)
This dissertation, in the domain of Architecture, approaches the working class neighborhoods, as an attempt to answer the housing problems established by the demands of the Industrial Revolution. This scarcity of workers' residence, exponentiated by the movement from the rural areas to the city, is portrayed through four spaces belonging to the county of Guimarães, built under the issue of industrialization in this region, in the early 20th century. Therefore, it is on the working class neighborhood that the Portuguese Industrial History is centered and its influence on the modification of the urban tissue, lecturing about the value of industrial philanthropy and the disparity between private intervention and public promotion for the construction of these factory workers cores. Thus, a succinct look will be yield on the social problems caused by this type of social ghettoization, being reinforced by the portrayal of the four cases we analyzed, the specific neighborhoods that will serve as basis for our generalization, supporting us in a theoretical and archival framework. The 'Casas da Tabela' (The Chart Houses) composes the project that leads us to mirror the issues of construction and their determination in ways of living, also serving as a specimen of the analysis on the adaptation of housing to contemporary needs. Accordingly, some notes about the current status of the neighborhoods will be referred, focusing on the remodeling operations and qualification projects.